2011
DOI: 10.1001/archneurol.2011.182
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Outcome of Subthalamic Stimulation in Parkinson Disease

Abstract: To assess the 10-year motor outcome of deep brain stimulation of the subthalamic nucleus (STN-DBS) in patients with Parkinson disease (PD). Design: Patients with PD with bilateral STN-DBS were assessed according to the Core Assessment Program for Surgical Interventional Therapies in Parkinson's Disease protocol and videotaped at baseline and 1, 5, and 10 years after surgery. An independent rater blinded to stimulation and medication condition scored the 10year video assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
342
3
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(396 citation statements)
references
References 23 publications
40
342
3
11
Order By: Relevance
“…Our findings agree with what observed in other studies [6], [7] and [8], and could be chiefly explained by the progression of the disease over time [16]. While the cardinal PD symptoms keep on improving with stimulation, there is a progressive emerging of poorly levodopa-responsive symptoms, mainly axial symptoms, speech problems and postural instability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings agree with what observed in other studies [6], [7] and [8], and could be chiefly explained by the progression of the disease over time [16]. While the cardinal PD symptoms keep on improving with stimulation, there is a progressive emerging of poorly levodopa-responsive symptoms, mainly axial symptoms, speech problems and postural instability.…”
Section: Discussionsupporting
confidence: 92%
“…STN-DBS efficacy on PD motor symptoms is well documented in the short-and medium-term, up to 5-6 years [4] and [5], while a few papers with a small number of examined patients addressed the long-term efficacy of this procedure [6], [7] and [8].…”
Section: Discussionmentioning
confidence: 99%
“…The subthalamic nucleus (STN) is a key structure in the basal ganglia-thalamo-cortical motor cir- cuit, and DBS of the STN showed striking improvements, of 41-55%, in motor function (5,(7)(8)(9)(10). The globus pallidus internus (GPi) is also an important stimulation target, demonstrating similar improvements in motor symptoms to STN DBS.…”
Section: Current Practice Of Stereotactic Ign Deep Brain Stimulation mentioning
confidence: 99%
“…Depression has been described as a common side-effect following STN DBS (Houeto et al, 2002). However, the pictures depicted by large randomized controlled trials (Deuschl et al, 2006;Witt et al, 2008;Weaver et al, 2009) and from long-term outcome studies Castrioto et al, 2011a) differ as, in the former, measures of depression were found to be slightly improved in the surgery group whereas in the latter depression was not described as a frequent sideeffect. The main risk factors for the occurrence of postoperative depression include preoperative history of depression, rapid or excessive dopaminergic medication withdrawal, and difficulties adjusting to life-changing surgery (Agid et al, 2006;Volkmann et al, 2010).…”
Section: Chronic Issuesmentioning
confidence: 99%